Two Instrumental Arrangements from Early Sixteenth-Century Bohemia - Kovarik, Edward (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
The Specialnik manuscript (HradKM II.A.7), from early sixteenth-century Bohemia, includes two well-known works with unique supplementary voices. One work, the final Agnus of Brumel's Missa Ut re mi fa sol la, includes an added bassus which deepens the composite range and animates the original without seriously disrupting it. An analysis of this movement shows why it was popular as an independent instrumental piece: it is clearly structured as statement and heightened reprise. The second work, Bedingham's "Fortune/Gentil madonna" contains a similar kind of bassus (as a substitute for the original contratenor) and also a triplum which exhibits characteristics of an idiomatic instrumental style. The Spec arrangement prompts a re-examination of the other sources and a demonstration that Bedingham's song originally called for a change from triple to duple mensuration in its B section.